1993
DOI: 10.1002/hep.1840170624
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid synthesis from newly synthesized vs. preformed cholesterol precursor pools in the rat

Abstract: The present study defines the origin of cholesterol subserving bile acid synthesis in male rats with an extracorporal bile duct by labeling newly formed cholesterol with tritiated water. Within 6 hr after interruption of the enterohepatic circulation, the bile acid pool was depleted. At this early time point the proportion from de novo cholesterol was 8% and 12% for biliary cholesterol and cholate, but 18% and 19% for muricholate and chenodeoxycholate, respectively. This proportion gradually rose to 40%, 34%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Under physiological conditions (6-9 hours), biliary secretion of de novo cholesterol amounted to no more than 18% in rats 45,47,55,56 and 5% in hamsters and humans. 44,57 Bile acid infusions did not significantly decrease biliary secretion of de novo cholesterol, suggesting that inhibition of cholesterol synthesis by bile acids may not be relevant in hamsters under these circumstances.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Under physiological conditions (6-9 hours), biliary secretion of de novo cholesterol amounted to no more than 18% in rats 45,47,55,56 and 5% in hamsters and humans. 44,57 Bile acid infusions did not significantly decrease biliary secretion of de novo cholesterol, suggesting that inhibition of cholesterol synthesis by bile acids may not be relevant in hamsters under these circumstances.…”
Section: Discussionmentioning
confidence: 95%
“…Using a further methanolpetroleum ether-extraction, both constituents were separated. The methanol phase served for high-pressure liquid chromatography (HPLC)-online liquid scintillation analysis of unconjugated bile acids 45 after they had been deconjugated enzymatically by 3␣-steroid dehydrogenase. Preceding an alkaline hydrolysis, biliary cholesterol was quantified from petroleum ether extract by a second HPLC-online liquid scintillation system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to studies by Hellerstein and Neese 39 and our own previous work, 9 [1][2][3][4][5][6][7][8][9][10][11][12][13] C]acetate was infused intraduodenally and not intravenously. Because of the preferential hepatic clearance of acetate from portal blood, 35,40 the dose could be reduced to one third of the amount given intravenously, and both experimental procedures resulted in comparable cytosolic [ 13 C]acetate enrichments.…”
Section: Discussionmentioning
confidence: 99%
“…In rats and hamsters the amount of newly synthesized cholesterol secreted into bile amounts to 8% to 18% and 2% to 5%, respectively. [3][4][5][6] In humans, most of the indirect evidence using standard radioisotope kinetics supported that 20% of biliary cholesterol were derived from de novo synthesis, 7 the majority being preformed cholesterol supplied by high-density lipoprotein cholesterol. 8 We have recently shown that the mass isotopomer distribution analysis (MIDA) technique allows for the direct measurement of the 4% to 5% of newly synthesized cholesterol formed from [ 13 C]acetate in bile and also that a significantly higher proportion of de novo cholesterol is secreted into bile as opposed to plasma in healthy individuals' circulation.…”
mentioning
confidence: 99%